Traditional knowledge research in India: A bibliometric-based review and thematic analysis - Shubham Anand
Traditional knowledge (TK) has gained substantial recognition for its utility in solution-seeking approaches to contemporary issues such as climate change, disaster risk resilience, and preservation of cultural identity. This makes it imperative to scrutinize the evolution of TK as a research field. However, there is a dearth of scholarly articles offering a holistic overview of TK-related research. The initial finding indicates that India is leading the field in such research among Asian countries. Consequently, the present study analyses the evolutionary trajectory of this research field in India, encompassing past, present and anticipated future discourse of such research. The present study employs insights from a bibliometric analysis of 836 literatures. Additionally, in-depth thematic analysis is based on the full-text review of 107 research papers. The study uncovers three prominent research themes emerging through the thematic analysis: (a) recording of TK through collation and documentation, (b) traditional medicinal systems, and (c) environment and sustainability. This critical exploration underscores the need for future research towards widening the scope of TK research, exploring the alternate forms of conservation, and deliberating on the efficient legal and policy measures aimed at uncovering the research field of TK while informing contemporary developments.